Herói como identidade cultural em discursos de terreiros - Oliveira, Jonatas Eliakim D Angelo de (2018)
The purpose of this dissertation is to examine the construction of the modern hero in terreiro discourses. In this sense, we propose to identify, in the umbanda point discourse, the modes of organization and inscription of the subjects in scenography and to verify the generic status of the selected discourses. The ethos that emerges in the discourses of social groups is related to the set of values and principles defended by socio-cultural identities. This aspect mobilizes the research on the organization of the genres of discourse enunciated by some identity groups to understand what are in them the regularities that allow us to verify the meaning effects of the emergence of such discursive ethos and to what extent this instance presents some of the aspects of cultural identity. For our study, we took as a theoretical-methodological reference the Discourse Analysis, especially the one practiced by Dominique Maingueneau (1997, 2000, 2001, 2004, 2007, 2008a, 2008b, 2009, 2010, 2015, 2016). Also, to capture the notions of hero, identity, crowd and modernity, the reflections produced in the theoretical frameworks of Cultural Studies, African Philosophy and Social Psychology were mobilized. The corpus, composed of nine chants of invocation belonging to the hymnal of the faithful of the Guaracy Temple of Brazil, allows us to identify the desired regularities and present the construction of the bond of identity necessary for the figure of the representative of the group, the hero, to be constituted